Aeroelastic Flutter of Subsonic Aircraft Wing Section with Control Surface (Journal of Engineering, 2015)
Aeroelastic flutter in aircraft mechanisms is unavoidable, essentially in the wing and control surface. In this work a three degree-of-freedom aeroelastic wing section with trailing edge flap is modeled numerically and theoretically. FLUENT code based on the steady finite volume is used for the prediction of the steady aerodynamic characteristics (lift, drag, pitching moment, velocity, and pressure distribution) as well as the Duhamel formulation is used to model the aerodynamic loads theoretically. The system response (pitch, flap pitch and plunge) was determined by integration the governing equations using MATLAB with a standard Runge–Kutta algorithm in conjunction with Henon’s method. The results are compared with previous experimental data. The results show that the aerodynamic loads and wing-flap system response are increased when increasing the flow speed. On the other hand the aeroelastic response led up to limit cycle oscillation when the flow equals or more than flutter speed.